(untitled) (Confluenţe Bibliologice, 2021)
The article presents the results of the online questionnaire School librarians during the pandemic, which included a series of questions related to the activity of these institutions during the pandemic, the services they managed to maintain, how they provided access to information to users, which were the most difficult aspects and what topics would need to be studied at the next professional meetings.